SDGs, Islamic banks and economic growth nexus: a case study of Malaysia - Abdul-Wahab, Abdul-Hamid (2022)
Purpose – The purpose of this paper is to examine the short-run and long-run relationships between Islamic banks’ financing that are aligned with the SDGs and economic growth in Malaysia. Design/methodology/approach – Utilizing quarterly data set for the duration of 2014 to 2018, this study applies the bound testing approach to cointegration and error correction model to analyse the data based on autoregressive distributed lag (ARDL) ARDL approach. Findings – The results suggest that Islamic banks’ financing in line with SDG2, SDG3, SDG4 and SDG11 have significant impact on economic growth in the short-run and long-run. However, while SDG2, SDG3 and SDG4 have negative impact on economic growth, SDG11 has a positive impact on economic growth. Research limitations/implications – Thoughtful policies to encourage Islamic banks’ financing in line with the SDGs while coping with slow economic growth will be imperative in achieving the SDGs in the long-run. This matters because with just eight years to go until the SDGs deadline of 2030, policymakers and Islamic banking regulators need to act fast by formulating strategies that will shift emphasis on GDP growth to financing the SDGs. Originality/value of the paper – This paper is a pinioning effort in the application of the ARDL approach to investigate the nexus between the SDGs, Islamic banks and economic growth.